Fast sorption measurements of volatile organic compounds on building materials: Part 1 – Methodology developed for field applications. (April 2016) - Rizk, M.; Verriele, M.; Dusanter, S.; Schoemaecker, C.; Le calve, S.; Locoge, N.
Abstract: Several physicochemical processes occurring within buildings are key drivers of indoor concentrations of Volatile Organic Compounds VOCs. Many models and experimental studies have been proposed to predict VOCs concentration indoors given these processes. However, there is a lack of representative data in literature to present gas–surface interaction in order to validate mathematical models. This work is divided in two parts and aims to develop and validate a method to perform fast measurements of VOC sorption parameters on the field by coupling a Field and Laboratory Emission Cell (FLEC) to a Proton Transfer Reaction-Mass Spectrometer (PTR-MS). In the part 1 of the work, sorption coefficients of aromatic compounds on a gypsum board and vinyl flooring were investigated at ppb levels to test and evaluate the proposed methodology. Sorption coefficients in the range of 0.03–1.88 m h −1 for ka and 2.04–17.32 h −1 for kd were successfully measured within a (0.5–8 h) for the two materials. Robustness tests highlight that the determination of sorption coefficients does not depend on operating conditions. While sorption coefficients for the gypsum board were measured with a PTR-MS time resolution of 20 s, the vinyl flooring material required measurements at a higher time resolution of 2 s due to its lower sorption properties. Limits of applicability assessed for this method indicate that sets of sorption parameters (ka, kd ) of (0.01 m h −1 ; 0.01 h −1 ) and (0.09 m h −1 ; 0.09 h −1 ) can be measured with an accuracy better than 10% at time resolutions of 2 and 20 s respectively. Graphical abstract: Highlights: Development of a new methodology to measure in-situ VOCs sorption on building materials. Evaluation of sorption parameters under real conditions within few hours. Measurement of low sorption properties with 10% of accuracy. Sorption parameters are useful to IAQ models to predict VOCs concentration indoors.